PERSEPSI MAHASISWA STIKES HARAPAN IBU JAMBI TERHADAP PEMBELAJARAN DARING VIA ZOOM PADA MASA PANDEMI COVID-19 - Deny Sutrisno; Lia Anggresani; Muammar Khadafi (Academy of Education Journal, 2022)
The purpose of this study was to determine the perceptions of Sekolah Tinggi Ilmu Kesehatan Ibu Jambistudents towards online learning via Zoom during the Covid-19 pandemic. Method. This research used descriptive method. The sample was collected using a non-probability sampling technique with an accidental sampling approach. The results of this study indicated that students' expectations of the use of zoom were to make online learning easier, used in theory learning and also for discussion with friends.